Depression and risk of sarcopenia: a national cohort and Mendelian randomization study - Zhong, Qian; Jiang, Lisha; An, Kang; Zhang, Lin; Li, Shuangqing; An, Zhenmei (Frontiers in Psychiatry, 2023)
Background: Depression and the increased risk of sarcopenia are prevalent among the elderly population. However, the causal associations between these factors remain unclear. To investigate the potential association between depression and the risk of sarcopenia in older adults, this study was performed.In the baseline survey, a total of 14,258 individuals aged 40 and above from the China Health and Retirement Longitudinal Study (2015) participated. We initially described the baseline prevalence of the disease. Then, logistic regression and restricted cubic spline (RCS) regression were conducted to assess the relationship between depression and sarcopenia. Subgroup analysis was performed to validate the robustness of the findings. Additionally, we conducted Mendelian randomization analysis using the inverse variance weighting estimator to assess the causal relationship between depression and sarcopenia. Furthermore, we adopted six methods, including MR-Egger, simple median, weighted median, maximum likelihood, robust adjusted profile score (RAPS), and MR Pleiotropy Residual Sum and Outlier (MR-PRESSO), for sensitivity analyses.Results: Depression patients exhibited higher risks of sarcopenia in all five models adjusting for different covariates (P < 0.05). The RCS analysis demonstrated a linear relationship between depression and sarcopenia (P < 0.05). In the subgroup analysis, increased risk was observed among participants aged 60-70, married or cohabiting individuals, non-smokers, non-drinkers, those with less than 8 hours of sleep, BMI below 24, and individuals with hypertension (all P < 0.05).Mendelian randomization results revealed that genetically proxied depression led to a reduction in appendicular skeletal muscle mass (all P < 0.05).Our study provides observational and causal evidences that depression can lead to sarcopenia. This finding emphasizes the importance of timely identification and management of depression, as well as implementing targeted educational programs as part of comprehensive strategies to prevent sarcopenia.